Potential Drug Candidates in Clinical Trials for the Treatment of Covid-19: An Updated Overview - Cáceres, Osmar Ignacio Ayala; Timóteo, Fernanda; Santos, Kristiane Fanti Del Pino; Vasconcelos, Rafael Rodrigo Piva; Martines, Marco Antonio Utrera; Jorge, Juliana; Rashid, Haroon ur (Orbital: The Electronic Journal of Chemistry, 2021)
The coronavirus (SARS-CoV-2) emerged in December 2019 in Wuhan, China and by the end of April 2020, it spread to more than 200 countries worldwide. Particularly the USA, Brazil, Spain, Italy, France, Germany, UK, Turkey, Iran, and Russia were the most affected countries till December 2020. Currently, most of the researchers are in a continuous struggle to develop a vaccine or new drugs to combat Covid-19. There are more than 30 drug candidates including Western medicines, natural products, and traditional Chinese medicines, that have shown to exhibit some efficacy against this highly infectious virus. This review encompasses the potential efficacy of some key drugs recently tested against Covid-19. With the rapid spread of Covid-19 reaching a new level every day, there is an immediate need to find safe and effective measures to diagnose, treat, mitigate, and combat the disease. Looking at the alarming dimensions that the disease is acquiring, treatment strategies among the different drug systems are being investigated. Currently, clinical management includes infection prevention, control measures, and supportive care, including supplemental oxygen and mechanical ventilation when indicated. The pharmaceutical interventions evaluated for the treatment of Covid-19 include human immunoglobulin, interferons, chloroquine, hydroxychloroquine, arbidol, remdesivir, oseltamivir, favipiravir, carrimycin, methylprednisolone, bevacizumab, thalidomide, vitamin C, pyrodfenidone, darthviravir, bromexistone, ryrexavir, lopinavir, xiyanping, and traditional Chinese medicine. But still, the researchers are struggling to discover the most effective drug for the treatment of the current pandemic of Covid-19. DOI: http://dx.doi.org/10.17807/orbital.v13i4.1638